2007
DOI: 10.1590/s0021-75572007000800005
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da internação em unidade de terapia intensiva pediátrica: avaliação por meio de escalas de desempenho cognitivo e global

Abstract: Objective: To assess the impact of admission to the pediatric intensive care unit (ICU) at the Hospital de Clínicas de Porto Alegre, RS, Brazil on children's cognitive and global performance.Methods: An observational, longitudinal study of a sequential sample of critically ill children. The following indicators were used: the Pediatric Index of Mortality (PIM), for severity and risk of death at admission, the Pediatric Cerebral Performance Category (PCPC), for cognitive morbidity and the Pediatric Overall Perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 18 publications
2
6
1
Order By: Relevance
“…In contrast to other studies that indicate a relationship between functional status at discharge, assessed by the Pediatric Cerebral Performance Category (PCPC) and the Pediatric Outcome Performance Category (POPC), and predictive mortality rates at admission, ( 5 , 14 , 15 ) in this study, we did not observe a significant difference in admission PIM2 values, according to the impairment in the overall FSS score presented by individuals at discharge from the PICU . This can be explained by Fonseca et al, ( 16 ) who verified that the PIM2 proved to be an inadequate measure to predict the mortality of patients with chronic conditions, which seems to be the case of the population in our study, in which only 16% individuals did not present any health condition prior to hospitalization in the PICU.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to other studies that indicate a relationship between functional status at discharge, assessed by the Pediatric Cerebral Performance Category (PCPC) and the Pediatric Outcome Performance Category (POPC), and predictive mortality rates at admission, ( 5 , 14 , 15 ) in this study, we did not observe a significant difference in admission PIM2 values, according to the impairment in the overall FSS score presented by individuals at discharge from the PICU . This can be explained by Fonseca et al, ( 16 ) who verified that the PIM2 proved to be an inadequate measure to predict the mortality of patients with chronic conditions, which seems to be the case of the population in our study, in which only 16% individuals did not present any health condition prior to hospitalization in the PICU.…”
Section: Discussioncontrasting
confidence: 99%
“…The median overall functional score and the percentage of individuals with normal FSS scores and overall FSS scores ≥ 20 found in our population were similar to the results of the original instrument study. ( 7 ) The main causes of admission to the PICU, such as respiratory failure, postoperative recovery, sepsis and shock, and liver failure, were similar to those of another study conducted in the PICU of HCPA, ( 5 ) likely due to the profile of the patients admitted in this unit.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…is was similar to a reference range of 54% to 84.3% [26,27]. However, the percentage of survivors with normal PCPC was lower for those admitted to the SUH PICU.…”
Section: Discussionsupporting
confidence: 79%
“…32 Other studies have reported the rate of new functional disability to be higher in PICU survivors (32%) compared with children with normal cognitive function (20%). 33 Knoester et al reported that an alarming 69% of children suffer physical and neurocognitive sequelae 3 months after PICU discharge, half of whom acquired these morbidities as a direct result of their critical illness. 34 …”
Section: The Post–intensive Care Syndrome In Childrenmentioning
confidence: 99%